Uma abordagem maker para o ensino de circuitos elétricos - Rocha, Patriky Souza (2024)
Given the difficulty that basic education students face in assimilating content that requires a certain level of abstraction, such as electricity, this work explores an experimental approach to the Teaching of Electricity with a focus on electrical circuits and resistors. Aiming to reduce this difficulty, a didactic sequence was developed involving experimental practices on electrical circuits using conductive ink. The ink is made with easily accessible and low-cost materials. The students autonomously produce both the circuits and the ink. This methodology, which introduces a “maker” approach, contributes to the construction of new knowledge in a creative and collaborative manner. In parallel, a theoretical teaching and learning framework based on Lev Vygotsky’s socio-interactionist theory was employed. As part of the pedagogical proposal, an educational booklet was created containing instructions and methods on how to make and use the conductive ink. Furthermore, it is divided into five experimental practices addressing topics such as resistors, resistor combinations, and electrical measuring instruments. At the end of each experiment, and throughout them, questionnaires were designed to help teachers assess the learning process of the students. The educational product was applied to a second-year high school class in a private school located in Caucaia-CE, with 16 students participating. The school did not have a science laboratory, but the application was adapted to take place in a regular classroom. During the application, strong social interaction was observed among the students, with the exchange of experiences about physical concepts and their illustrations using the ink, creating an interactive and welcoming environment throughout the practices. From the students’ notes, it was observed that they gained practical insight into theoretical concepts, as well as a qualitative understanding of the physical phenomena of electrical circuits, leading to a better comprehension of the content related to electrical circuits.